SEBARAN LOGAM BERAT CADMIUM (Cd) DAN TIMBAL (Pb) PADA AIR SUNGAI DAN SUMUR DI DAERAH SEKITAR TEMPAT PEMBUANGAN AKHIR (TPA) WUKIRSARI GUNUNG KIDUL, YOGYAKARTA - Eko Siswoyo; Ghozi Faiz Habibi (Graduate School Bogor Agricultural University (SPs IPB), 2018)
Cadmium (Cd) and Lead (Pb) are heavy metal which is very harmful for human being even though in low concentration. Leachate from municipal landfill is one of heavy metals source and its presence often caused environmental contamination in Indonesia and also many countries. Therefore, study on the distribution of Cd and Pb around landfill area is important to be conducted. Based on the distance between location of Wukirsari landfill and sampling points, samples were taken from river and ground water and then analyzed by using atomic absorption spectroscopy (AAS) instrument in order to know the concentration of Cd and Pb ions in water. In order to know the effect of weather, samples from 10 different sampling points were taken during dry and rainy seasons (two times sampling for each season). The concentration of Cd in the river and ground water is in the range of 0.001-0.03 mg/l and 0.01-0.53 mg/l for Pb (higher than the government standard). The concentration of Cd and Pb decreased during rainy season because of dilution from rain water. The results of this study show that treatment of leachate is urgent to minimize the contamination of heavy metals and negative impact to human being. Constructed wetland could be considered as an appropriate treatment for effluent of leachate treatment plant at landfill.